Perlindungan Hukum Terhadap Indikasi Geografis di Kabupaten Jayapura - Irianti, Y.D.W. Susi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out, analyze and explain the mapping of geographical indications in Jayapura Regency and the legal protection of Geographical Indications in Jayapura Regency. The type of research used is empirical legal research because it is motivated by the idea that law cannot be separated from people's lives in the form of values and attitudes/behavior carried out (law is not autonomous) which can be seen in reality in people's lives. The results of the research reveal that efforts to map geographical indications were carried out to determine the boundaries of cases of violation of geographical indications so that geographical indication rights holders can file lawsuits against users of geographical indications without rights, in the form of payment of compensation and termination. Use and destruction of geographic indication labels that are used without authorization through registration and publication. Geographical indications are protected as long as the reputation, quality and characteristics that are the basis for granting geographical indication protection to an item are maintained and protection will be removed if these provisions are not fulfilled, and/or conflict with state ideology, legislation, morality, religion, decency and public order. . Therefore, geographical indication mapping must be organized in geographical indication documents whose veracity can be proven. Identified procedures for applying for geographical indications and procedures for registering geographical indications. Legal protection for geographical indications can be carried out in preventive and repressive forms. Preventive, namely preventive measures through refusal of registration and repressive payment of compensation.